Biomaterial-based cell delivery strategies to promote liver regeneration. - Ali, Maqsood.; Payne, Samantha L. (Tufts University. Tisch Library., 2021)
Keywords: Two dimensional, Three dimensional, Bone morphogenetic protein, Cluster of differentiation 44, Endothelial cell, Extracellular matrix, Epithelial growth factor, Epithelial growth factor receptor, Epithelial cellular adhesion molecule, Embryonic stem cell, Fibroblast growth factor, Granulocyte colony-stimulating factor, Hyaluronic acid, Hepatocyte, Hepatoma G2, Hepatocyte growth factor, Hedgehog, Human induced pluripotent stem cell, Hepatic stem cell, Human umbilical vein endothelial cell, Interferon-γ, Insulin growth factor, Interleukin, Kupffer cell, Leucine-rich repeat-containing G-protein coupled receptor, Lipopolysaccharide, Liver sinusoidal endothelial cell, Lymphotoxin-α, Mesenchymal stem cell, Myeloid differentiation primary response 88, Orthotopic liver transplantation, Poly(Ɛ-caprolactone), Poly (ethylene glycol) diacrylate, Polyglycolic acid, Partial hepatectomy, Polylactic acid, Poly(L-lactic acid)-co-poly (Ɛ-caprolactone), Poly (lactic-co-glycolic acid), Poly-L-lactic acid, Stem cell factor, Transforming growth factor-β, Toll-like receptor 4, Tumor necrosis factor receptor 1, Tumor necrosis factor-α, Vascular endothelial growth factor, Wingless-related integration site.; Springer Open.